Penerapan Model Komunikasi Schramm Pada Pembelajaran Teks Berita Kelas VII di SMP Islam Bungoro - Al-Munawarah, Syayidatul Zuhrah; Salam, Salam; Usman, Usman (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the implementation process and learning assessment by applying Schramm's communication model in learning news text. This research uses descriptive qualitative research. The focus of this research is the application of Schramm's communication model to VIII grade students in learning news texts at SMP Islam Bungoro and the assessment used in its application. Data collection techniques in this study were carried out in three stages, namely; observation, interview, and documentation. The research instruments used in this study are researchers who act as human instruments and auxiliary instruments in the form of observation sheets, interview guidelines and Learning Implementation Plan (RPP) instruments. The process of implementing learning by applying the Schramm communication model is carried out through two stages, namely planning and implementing learning. The results showed that the application of Schramm's communication model in learning was effective enough to be used in the learning process to further increase the intensity of communication between teachers and students. Learning assessment by applying the Schramm communication model to students includes four dimensions, namely KI-1 spiritual attitude, KI-2 social attitude, KI-3 knowledge, and KI-4 skills.